2021
DOI: 10.1038/s41598-020-79796-9
|View full text |Cite
|
Sign up to set email alerts
|

Intentional synchronisation affects automatic imitation and source memory

Abstract: Acting in synchrony is a fundamental part of many social interactions and can have pro-social consequences. Explanations for this relationship were investigated here using implicit measures of imitation (automatic imitation task) and memory (preference overlap task). In Study 1, participants performed an intentional synchronisation task where they moved sliders in or out of time with another person while a third person observed. Those who had moved in synchrony showed a stronger tendency to imitate their partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…An example of this is that synchronous walking, or cup waving and singing, results in participants making more cooperative choices in subsequent economic games, even if such choices come at a real financial cost to them [13]. Other research has shown that after moving synchronously together, participants are more likely to help their co-actors, even some time after the initial coordination task [14], as well as to conform and obey their requests [15,16], and show better memories for co-actors [17][18][19].…”
Section: Introductionmentioning
confidence: 97%
“…An example of this is that synchronous walking, or cup waving and singing, results in participants making more cooperative choices in subsequent economic games, even if such choices come at a real financial cost to them [13]. Other research has shown that after moving synchronously together, participants are more likely to help their co-actors, even some time after the initial coordination task [14], as well as to conform and obey their requests [15,16], and show better memories for co-actors [17][18][19].…”
Section: Introductionmentioning
confidence: 97%
“…For instance, adults exhibit increased feelings of bonding, trust, empathy, and pro-social behaviours following interpersonal synchrony [12][13][14][15][16] . Adults are also more likely to imitate a partner after engaging in a synchronous movement task with them as compared to after performing those movements asynchronously with their partner 17 . Similarly, in children, interpersonal synchrony has been shown to facilitate pro-social sharing 18,19 and helping behaviour 5 .…”
mentioning
confidence: 99%
“…Synchrony is a basic process in human communication that takes place immediately after birth within mother–child interactions 7 . It has a crucial role in the process of forming interpersonal relationships 8 , 9 and serves as an integral part of our social behavior and cognition 1 , 10 . Specifically, motor synchrony facilitates pro-social behavior 11 , 12 as well as enhances liking 13 15 , trust 16 , and cohesion 13 , 17 , 18 between individuals interacting face-to-face.…”
Section: Introductionmentioning
confidence: 99%